Students’ Perception and Motivation of Online Google-Meet App on Learning English during Covid-19 Period - Anita; Kheryadi; Qurrotu Aini Aini (ELITE Association Indonesia, 2021)
This research investigated about student’ perception and motivation of Google-meet on learning English during covid-19 period. The aim of this research is to investigate how are students’ perception and motivation in using Google-meet. In this research, qualitative approached used to investigate students’ perception and motivation. In this research uses questionnaire and interview to collecting the data. From the finding, the researcher found positive perception and high motivation of students of the use of Google-meet as media in learning English during Covid-19. The positive perception are good quality of interact, effective the teaching, saving the time and energy, eliminate inconvenience to practice English, and easy to use. In beside that the students’ high motivation are interesting of app, increase of ambition and awareness and also physical condition in intrinsic motivation. Meanwhile, get kew knowledge, social condition and supporting facilities in extrinsic motivation. Keywords: Perception, Motivation, Google Meet, E-Learning